Blooming together or wilting alone? Network externalities and Mondragón and La Lega co-operative networks - Stephen C. Smith (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper examines strategies developed by Mondragón Co-operative Corporation in the Basque Region of Spain, and La Lega co-operative network in Italy, to mitigate disadvantages of the typical co-operative organizational structure and market position but without losing its critical advantages and attractive features. A detailed institutional overview of these most prominent examples of successful co-operative clusters is presented. The paper argues that there are network externalities in co-op formation and survival, that imply that even if other barriers to entry are overcome and a co-op is established it may not survive, not because of intrinsic inefficiencies, but simply because of the lack of other co-operative entry, and to some extent also because of a lack of coordination among co-ops that do enter the market. The central hypothesis of this paper is that co-op leagues can help to internalize these externalities, and its application is to show how this has been accomplished in practice, at least in part. The paper examines recent institutional responses to increasing global competition and requirements to improve access to finance and accelerate the pace of innovation and the improvement of product quality within La Lega and Mondragón. A systematic comparison of these two networks is presented along ten dimensions selected either for their role in the theoretical literature on co-operatives, labour managed and similar firms, or for their prominence in the formal structures of one or both networks; in each case the role of co-op networks, whether through consortia or industry, regional or national associations is highlighted. The paper concludes by exploring the implications of the institutional innovations of these networks for the ownership restructuring of enterprises in transition economies with substantial employee ownership, such as Russia, and developing countries with significant co-operative systems, such as India. – Mondragón ; La Lega ; co-operative network ; co-operatives ; employee ownership ; labour managed firm ; Italy ; Spain ; developing countries ; economic development ; transition
Keywords: J54; L2; O12; 330; Genossenschaft; Network Externalities; Spanien; Italien